Risk perception and specific behaviors of anglers concerning mercury contamination of fish. Issue 4 (20th April 2020) - Gilfriche, Pierre; André, Jean-Marc; Gentes, Sophie; Maury-Brachet, Regine; Legeay, Alexia; Feurtet-Mazel, Agnes; Lespinet-Najib, Véronique
Abstract: In recent years, mercury levels in some predatory fishes of several lakes of South-West France, exceeding the European Union nutritional recommendations threshold for safe consumption have been noticed. This led to a decision by regional authorities to ban consumption of those species. We conducted a questionnaire-based study on 276 users of four lakes of the region, two of which were affected by the ban, in order to better understand how it had affected perception of the risk and the associated behaviors. Our study revealed that anglers were the major fish consumers. It also showed that the ban had a poor impact on anglers' actual fish consumption, despite their being globally well informed about its existence. We conclude that the ban has had a weak impact on anglers' perception of risk, and that safety nutrition policies should better take into account this factor in the future.